(untitled) (Andamios, Revista de Investigación Social, 2010)
An economic crisis can highlight some of the excesses that must be fought in the present and avoided in the future. They are not a consequence of the action of a specific or particular thought. This paper pays attention to different voices: those who ask for the right to credit, those who want a limit to private property, and those who demand responsibilities from one to another, and who present other development models.